Problème de Contact Entre Deux Corps Électro-élastiques avec Adhésion - Ibtissam, Greid; Rim, Kordi Souad (My University, 2022)
In this memory , we studied the problem of mechanics in contact with adhesion for the electro-elasticity constitutive laws. We used Green’s formula to obtain the variational formulation of this problem. We have shown the existence and uniqueness of the solution from the previous problem by using the following arguments: time-dependent variational equation, the theory of evolutionary . variational inequalities, parabolic inequalities and fixed point theoryفً هذه المذكرة ،درسنا مشكلة التالمس المٌكانٌكً مع االلتصاق .تم استخدام صٌغة جرٌن للحصول على الصٌغة المتغٌرة لهذه المشكلة . أظهرنا وجود الحل و وحدانٌته للمسألة السابقة باستخدام الحجج التالٌة : المعادلة المتغٌرة المعتمدة على الوقت ،نظرٌة عدم المساواة التفاضلٌة القابلة للقٌاس ، من عدم المساواة فً القطع المكافئ و نظرٌة النقطة الثابتة
mémoier master mathématique
Keywords: Eléctro-élastique, adhésion, inégalité variationnaire évolutive, la théorie point fixe.; االلتصاق ، التفاوت التطوري المتغٌر ، نظرٌة النقطة الثابتة .